2017
DOI: 10.4236/oalib.1103266
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvest Season and Maturation of Different Sugarcane (Saccharum Spp.) Cultivars on the Chemical Composition of Alembic Brazilian Sugarcane Spirit

Abstract: Contrary to the ethanol industrial production, the quality and composition of sugar cane as raw material for the production of alembic cachaça have until now not been completely addressed. This work evaluated the influence of five different sugarcane cultivars and degree of maturation over the physicochemical composition of cachaça produced under strict controlled conditions. Three harvest seasons were used in order to obtain different stages of maturation. The sugarcane quality was assessed by the juice brix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the second harvest the amplitude was higher, being the variety CTC7 the one to present the highest average (Table 4). Fernandes et al (2017) and Ftwi et al (2017) also obtained great variation among the varieties in the conduction of different crop seasons for this trait when evaluating the genotypes x environments interaction in sugarcane. Means followed by the same lowercase letter in the column and upper case in the row belong to the same group, according to the Scott and Knott (1974) criterion at 5% probability (p <0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the second harvest the amplitude was higher, being the variety CTC7 the one to present the highest average (Table 4). Fernandes et al (2017) and Ftwi et al (2017) also obtained great variation among the varieties in the conduction of different crop seasons for this trait when evaluating the genotypes x environments interaction in sugarcane. Means followed by the same lowercase letter in the column and upper case in the row belong to the same group, according to the Scott and Knott (1974) criterion at 5% probability (p <0.05).…”
Section: Resultsmentioning
confidence: 91%
“…Ferreira et al (2005) when studying the repeatability and predictability for industrial variables in sugarcane also obtained high values for this parameter for most of the assessed traits. According to Fernandes et al (2017), high values for the repeatability coefficient is indicative of the performance regularity of the genotypes in the different crop seasons. Resende (2002) consider that values above 80%, for the coefficient of determination parameter, are considered appropriate for the selection of genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of sugarcane variety is the most important and least costly step in cachaça production. A study that evaluated sugarcane varieties, harvested at different times for cachaça production, showed that sugarcane variety influences the chemical composition of sugarcane juice and subsequently the product (Fernandes et al, 2017).…”
Section: Planting Harvesting and Milling Of Sugarcanementioning
confidence: 99%
“…There are no reports of intentional inoculation of lactic acid bacteria to cachaça fermentation must and this practice is not foreseen in its production process. However, ethyl lactate has already been identified in samples of cachaça (Nascimento et al, 2008;Fernandes et al, 2017;Karp et al, 2019). So far, however, the occurrence of this ester has been interpreted only as an indicator of failures in the cleaning of sugarcane juice, which should be remedied with the technological advancement of the sector.…”
Section: Introductionmentioning
confidence: 99%